Physical fitness and athletic performance - Watson, A. W. S., 1941- (London ; New York : Longman, 1995)
This book is about: Components of pfysical fitness; Principles of trainning, warm-up, motor unit types, sources of information; Training methods; Evaluation of fitness levels; and Sports injuries and their prevention.
Keywords: Physical education and training; Physical fitness; Physical education and training; Physical fitness -- Testing